The Signaling Power of Specially Designated Dividends - Gombola, Michael J.; Liu, Feng-Ying (Journal of Financial and Quantitative Analysis, 1999)
We distinguish among the signaling, free cash flow, and wealth transfer hypotheses in explaining the stock price reaction to specially designated dividend (SDD) announcements. In a direct test of the signaling power of SDDs, we find both a larger stock price reaction and a significant upward revision of earnings forecasts for firms with Tobin's q less than one, but not for other firms. Our results support the conditional signaling hypothesis, which predicts greater effects of favorable information for low q firms. Taken together, our results for stock price effects and earnings forecast revisions do not support either the free cash flow or wealth transfer hypotheses.